Investigation of surface potential of GaAs surface by means of acoustoelectric effects - PUSTELNY, T.; KUBIK, Z. (Archives of Acoustics, 1994)
The methods of surface potential determination of the semiconductor using the measurements of longitudinal and transverse acoustoelectric effects in the piezoelectric-semiconductor layer structure are presented. When a semiconductor sample is placed in the proximity of a piezoelectric surface acoustic wave (SAW) delay line, the propagating electric field interacts with the carriers in the semiconductor surface. As the results of these interactions the longitudinal and transverse acoustoelectric effects are observed. The acoustoelectric voltages are strongly dependent on the electrical properties of the near-surface region in semiconductor. The experimental results of investigations of the surface potential obtained for several GaAs samples are presented. For all various doped GaAs samples the values of the surface potential of real GaAs surfaces obtained by means of the new acoustic methods were nearly 0.4 [V].